Antimicrobial Activity, Phytochemical Analysis and HPLC Screening Of Cleomeviscosa. L (BioMedical Research in Microbiology (BMR Microbiology) (ISSN: 2349-4603), 2024)
The study was aimed to investigating the antimicrobial screening of ethanolic extracts of Cleome viscose against pathogenic bacteria and fungi responsible for common infections. The present investigation may be concluded that the plant Cleome viscosa is endowed with significant antimicrobial due to the presence of active constituents, there by justifying its use in the indigenous system of medicine.The seeds of Cleome viscosa are used in traditional systems of medicine for the treatment of many diseases in Asia. The present research work was conducted to investigate the invitro antimicrobial activity of seed extracts of plant Cleome viscosa. The ethanol extract of seeds of plants were screened against microbial species. The test materials have showed the significant antimicrobial activity. The zone of inhibition is found to be (12mm to 23 mm) bacteria and fungi. The present research work was identified phytochemical test presence of active biomolecules such as Alkaloid, tannins flavonoids, Fixed oil and fats, Gum and mucilage, sterols were present in water extracts of Cleome viscosa. To perform the solvent extraction and evaluate the Infra-Red and HPLC analysis.